IITA welcomes delegates from Groupe Nutriset, Nutrik, and Sow AgriTech Ltd - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
IITA welcomed delegates from Groupe Nutriset, NutriK, and Sow AgriTech Ltd to explore opportunities for stronger collaborations in nutrition, Ready-to-Use Therapeutic Foods (RUTF), and agricultural value chains. The visit focused on opportunities to scale groundnut production. The group also indicated interest in soybeans, cassava, and plantains, as well as short-term partnerships with IITA's Seed Tracking Program and Youth in Agribusiness initiatives.